2014
DOI: 10.1161/circulationaha.114.009468
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Long Detection Interval Implantable Cardioverter-Defibrillator Settings in Secondary Prevention Population

Abstract: Background-Three trials demonstrated recently that a long detection window reduces implantable cardioverter-defibrillator (ICD) therapy in primary prevention patients. Avoid Delivering Therapies for Nonsustained Arrhythmias in ICD Patients III (ADVANCE III) was the only trial that enrolled both primary and secondary prevention patients. Methods and Results-Of the 1902 patients enrolled in the ADVANCE III trial, 477 received a defibrillator for secondary prevention; 248 patients were randomly assigned to a long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…The findings of the Avoid Delivering Therapies for Nonsustained Arrhythmias in ICD Patients ADVANCE trial 10,11 also support the findings of the present study. Specifically, that the trial indicated that programming long detection intervals reduced the number of inappropriate shocks, but did not reduce mortality 10,11 .…”
Section: Association Between Inappropriate Therapy and Mortalitysupporting
confidence: 89%
See 2 more Smart Citations
“…The findings of the Avoid Delivering Therapies for Nonsustained Arrhythmias in ICD Patients ADVANCE trial 10,11 also support the findings of the present study. Specifically, that the trial indicated that programming long detection intervals reduced the number of inappropriate shocks, but did not reduce mortality 10,11 .…”
Section: Association Between Inappropriate Therapy and Mortalitysupporting
confidence: 89%
“…Conversely, one study has demonstrated that appropriate or inappropriate shocks are one of the risk factors for prognosis 7 , and subanalysis of data from MADIT-and SCD-HeFT showed a two-fold increased risk of death in patients who experienced inappropriate ICD shocks 8,9 . New strategies, changing the detection time and zone for ventricular arrhythmia, have been proposed to reduce inappropriate shocks [10][11][12][13] .…”
Section: Originalmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ADVANCE III Secondary Prevention substudy confirmed the safety of not programming therapy for rates patient-years [105]. Previously published recommendations suggest a VT zone starting at 10 to 20 bpm slower than the observed tachycardia rate, usually including a 2-or 3-zone arrhythmia detection scheme (as discussed elsewhere) [106].…”
Section: Rate Criteria For the Detection Of Ventricular Arrhythmiamentioning
confidence: 93%
“…56,57 These studies had a significant impact on ICD programming strategies, and spawned a number of similar studies examining variations on lenient programming practices. Several studies have examined high rate programming, 58,59 while others have considered prolonged detection, [60][61][62][63][64][65] or a combination of these two approaches. 66,67 In general, lenient programming practices in these studies have demonstrated a decrease in the rate of appropriate and inappropriate shocks, with either a decrease in overall mortality or no difference, when compared to conventional programming practices.…”
Section: Device-based Interventions-data From Studies In Adult Patientsmentioning
confidence: 99%